EL CONTRATO COMO ORIGEN DE LAS SOCIEDADES MERCANTILES, EN EL DERECHO ESPAÑOL - COMPARACIÓN CON EL DERECHO PERUANO - Garcia Pita, José Luis (Revista de Derecho, 2019)
The obvious and undeniable peculiarities that distinguish a company’s foundation act from the traditional bilateral contract have led to the apparition of different theories about the legal nature of such act at various times and places. Many of them have in common the denial of its contractual character. However, a more careful analysis allows to unequivocally assert that character, and thus the full validity of the traditional concept of “company contract”, its plurilateral nature (“two or more people”) and its radial structure (“who bind themselves to put jointly”). An indeed exceptional case —and yet, equally contractual in nature— may be found in the very special instance of the so-called successive foundation of companies.